2013
DOI: 10.1016/j.apmr.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Muscle and Skin Perfusion Over the Ischial Tuberosities in Response to Wheelchair Tilt-in-Space and Recline Angles in People With Spinal Cord Injury

Abstract: Objective To compare the efficacy of wheelchair tilt-in-space and recline on enhancing muscle and skin perfusion over the ischial tuberosities in people with spinal cord injury (SCI). Design Repeated measures and before-after trial design. Setting University research laboratory. Participants Power wheelchair users with SCI (N=20). Interventions Six combinations of wheelchair tilt-in-space and recline angles were presented to participants in a random order. The testing protocol consisted of a baseline 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Wheelchair recline was defined as “a change in seat to back angle while maintaining a constant seat angle with respect to the ground” [4, 5]. Configurations of tilt and recline are shown in Figure 2 and also described in our previous studies with the exception of recline measurements [14, 28, 29]. Previously, we reported recline measurements as the angle between the seat and the back support.…”
Section: Methodsmentioning
confidence: 99%
“…Wheelchair recline was defined as “a change in seat to back angle while maintaining a constant seat angle with respect to the ground” [4, 5]. Configurations of tilt and recline are shown in Figure 2 and also described in our previous studies with the exception of recline measurements [14, 28, 29]. Previously, we reported recline measurements as the angle between the seat and the back support.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that the shape of the wheelchair backrest affects the seated posture and the sitting-related problems of the user [17][18][19][20][21][22]. For instance, increasing the backward inclination of the backrest above 120° reduced buttock pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia and reperfusion injury is considered important in venous ulcer pathology, sickle cell and vasculitic ulcers, and pressure ulcers. Variations in muscle and skin fl ow, for example, are critical when deciding on sitting protocols for paraplegic patients to prevent pressure ulcer formation [ 10 ]. Improved diagnostic and therapeutic options for this condition will allow us to strategize our treatment plan.…”
Section: Treatment Optionsmentioning
confidence: 97%